A Rock Music As Extracurricular Music Material To Improve Musical Abilities At Al-Azhar 13 Smp Surabaya (Case Study Of Altera Band) - Bintari Purwasari, Riki; Sugito, Tomy (Solah, 2026)
This study aims to analyze the implementation of rock music material in extracurricular activities at SMP Al-Azhar 13 Surabaya and its impact on improving students’ musical abilities, particularly in the Altera band group. The background of this study is the need for innovation in music learning to be more contextual to students’ interests and able to optimally develop their musical potential. The study used a qualitative approach with observation, interview, and documentation methods, and data validation through triangulation of sources and techniques. The results show that the implementation of rock music is carried out through structured exercises, the selection of appropriate repertoire, and teaching strategies that encourage student creativity. This process contributes to improving technical abilities, understanding of rhythm and harmony, and teamwork in musical performance. Furthermore, these activities foster students’ self-confidence and sense of responsibility in music. The findings of this study confirm that rock music can function as an effective, creative, and contextual learning medium in music education. More broadly, this study contributes to enriching modern music pedagogical approaches by integrating popular genres into formal educational environments.